2016
DOI: 10.3945/ajcn.116.132589
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of vitamin D replacement on indexes of insulin resistance in overweight elderly individuals: a randomized controlled trial

Abstract: Vitamin D3 at 3750 IU/d did not improve HOMA-IR compared with the Institute of Medicine Recommended Dietary Allowance of 600 IU/d in elderly overweight individuals. This trial was registered at clinicaltrials.gov as NCT01315366.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…A total of 35 subjects, 14% of original randomized cohort, did not complete the study; the dropout rate was similar in both groups, most of it occurred early in the study, and was in large part due to patients having changed their mind about study participation (Fig. ) . Two patients died, one in each treatment group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 35 subjects, 14% of original randomized cohort, did not complete the study; the dropout rate was similar in both groups, most of it occurred early in the study, and was in large part due to patients having changed their mind about study participation (Fig. ) . Two patients died, one in each treatment group.…”
Section: Resultsmentioning
confidence: 99%
“…The trial had two primary outcomes, indices of insulin resistance at 12 months, recently reported, and of bone metabolism at 12 months reported herein (BMD and bone remodeling)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mixed, there is evidence linking elevated serum PTH and lower 25OHD to a variety of negative health outcomes in both men and women [43,44,45,46,47,48,49,50,51,52]. Some researchers hypothesize excess PTH secretion to be involved in the development of hypertension, a theory supported by data indicating a positive correlation between blood pressure and serum concentrations of PTH [53,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In several large community based cohort studies, low serum 25OHD levels have not shown to be associated with poor CVD outcomes [45,47]. The relationship of low serum 25OHD levels and insulin resistance and metabolic syndrome has been more consistently reported [48,49], although prospective studies do not always suggest improvements in insulin sensitivity with improvements in vitamin D status [50,51]. Whether or not the dosages used in these studies and effective in raising serum 25OHD levels is often debated.…”
Section: Discussionmentioning
confidence: 99%